2015
DOI: 10.1136/bmjopen-2014-006407
|View full text |Cite
|
Sign up to set email alerts
|

Why do some people with type 2 diabetes who are using insulin have poor glycaemic control? A qualitative study

Abstract: ObjectiveTo explore factors influencing poor glycaemic control in people with type 2 diabetes using insulin.Research designA qualitative method comprising in-depth individual interviews. A semistructured interview guide was used. The interviews were audiorecorded, transcribed verbatim and analysed using a thematic approach.ParticipantsSeventeen people with type 2 diabetes using insulin with glycated haemoglobin (HbA1c) ≥9% for >1 year.SettingThe Primary Care Clinic and Diabetes Clinic in the University of Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 25 publications
3
59
1
7
Order By: Relevance
“…These cases indicate that lack of insulin related knowledge in some patients resulted in insulin use disorders or poor adherence. These concerns are likely to affect patients' use of insulin, resulting in poor control of blood sugar 22. Intensive therapy with insulin in patients with type 1 diabetes was associated with a substantial reduction in the long term risk of ocular surgery 23.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cases indicate that lack of insulin related knowledge in some patients resulted in insulin use disorders or poor adherence. These concerns are likely to affect patients' use of insulin, resulting in poor control of blood sugar 22. Intensive therapy with insulin in patients with type 1 diabetes was associated with a substantial reduction in the long term risk of ocular surgery 23.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that some DM patients had concerns about the use of insulin. Tong et al 22 reported that psychosocial and emotional barriers were associated with poor glycaemic control in people with type 2 DM using insulin. Such psychological concerns leading to poor glycaemic control could promote the progression of DR.…”
Section: Discussionmentioning
confidence: 99%
“…The variable of occupation was significantly associated with glycemic control for housewives/students. Other studies (8)(9)17) have suggested that having an occupation (represented in the forms of occupation and housewife/student categories) corresponds to a risk factor for the occurrence of inadequate glycemic control. This may be associated with the fact that people with DM that have an occupation have less free time to manage and monitor their illness (8) , a justification also applied to housewives and students.…”
Section: Discussionmentioning
confidence: 99%
“…• Fear of side effects such as weight gain, hypoglycaemia (Tong, Vethakkan, & Ng, 2015;Wong et al, 2011;Funnell, 2007) • Fear of needles, experiencing pain at the injection site and injecting themselves (Tong et al, 2015;Wong et al, 2011;Funnell, 2007;Abu et al, 2013) • Social stigma associated with insulin use Funnell, 2007;Abu et al, 2013) Change perception through patient education • Engage and educate patients in the early stages of diabetes on how to achieve optimal glycaemic control • Emphasise the long-term benefits of timely insulin intervention • Use web-based technology to enable education of a larger number of patients…”
Section: Barriers Solutionsmentioning
confidence: 99%